Alfvén waves as a solar-interplanetary driver of the thermospheric disturbances - Guo, Jianpeng; Wei, Fengsi; Feng, Xueshang; Liu, Huixin; Wan, Weixing; Yang, Zhiliang; Xu, Jiyao; Liu, Chaoxu (Scientific reports, 2016)
Alfvén waves have been proposed as an important mechanism for the heating of the Sun’s outer atmosphere and the acceleration of solar wind, but they are generally believed to have no significant impact on the Earth’s upper atmosphere under quiet geomagnetic conditions due to their highly fluctuating nature of interplanetary magnetic field (i.e., intermittent southward magnetic field component). Here we report that a long-duration outward propagating Alfvén wave train carried by a high-speed stream produced continuous (~2 days) and strong (up to ±40%) density disturbances in the Earth’s thermosphere in a way by exciting multiple large-scale gravity waves in auroral regions. The observed ability of Alfvén waves to excite large-scale gravity waves, together with their proved ubiquity in the solar atmosphere and solar wind, suggests that Alfvén waves could be an important solar-interplanetary driver of the global thermospheric disturbances.